2016
DOI: 10.2174/1874944501609010088
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Infertility Among Couples in Ouagadougou (Burkina Faso): a Population-based Survey

Abstract: Abstract:Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(29 reference statements)
0
3
1
Order By: Relevance
“…The finding of this study is higher than that of a study performed in China in which the prevalence of infertility was 22.1% [ 33 ]. It is also higher than a similar study done in Cameroon in which the prevalence of infertility was 19.2% [ 34 ], also higher than a study done in Burkina Faso[ 35 ]. However, the finding of this study is much lower than the finding of a study done in Central Africa with a prevalence of 61% secondary infertility.…”
Section: Discussioncontrasting
confidence: 57%
“…The finding of this study is higher than that of a study performed in China in which the prevalence of infertility was 22.1% [ 33 ]. It is also higher than a similar study done in Cameroon in which the prevalence of infertility was 19.2% [ 34 ], also higher than a study done in Burkina Faso[ 35 ]. However, the finding of this study is much lower than the finding of a study done in Central Africa with a prevalence of 61% secondary infertility.…”
Section: Discussioncontrasting
confidence: 57%
“…Two studies in India reported infertility rate of 12.6% and 14.2% respectively (14,15). Another study conducted in Ouagadougou (Burkina Faso); the medically-diagnosed infertility prevalence was 2.9% (16). Thus, the prevalence of infertility varies between countries and in between the different parts of the same country; in addition, the large variation in inclusion criteria between different studies making comparison difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Öztekin et al, noticed primary infertility in 77.3% and secondary infertility in 22.7% [10]. Eric et al identified primary infertility of 52.3% [11]. Deshpande et al, showed that 57.5% of patients had primary infertility and 42.5% presented as secondary infertility [12].…”
Section: Discussionmentioning
confidence: 99%